Centrality measures for Shariah-compliant securities listed on Bursa Malaysia - Bahaludin, Hafizah; Mahamood, Fatin Nur Amirah; Abdullah, Mimi Hafizah; Fauzi, Muhammad Ashraf; Omar, Mawardi (Universiti Putra Malaysia, 2023)
An interrelationship between each of the specified Bursa Malaysia’s securities can be calculated using the correlation measure. However, there were a considerable number of these securities, thus, making it difficult to visualise their correlation. To overcome this issue, this association could be illustrated as a single network based on its correlation input. This research constructed a network between the securities listed on Bursa Malaysia, which centred on the Shariah-compliant stocks. Seven centrality measures, such as degree, betweenness, closeness, eigenvector, eccentricity, strength, and average of weight centrality, were used to determine the primary node of the network. The analysis utilised one hundred and 21 stocks from 2008 to 2018, which was divided into two periods, namely, during and after the 2008 global financial crisis (GFC). Additionally, the principal component analysis (PCA) was adopted to determine the main hub’s transformations during these two intervals. Finally, this study provided the market participants with valuable information established in a network for the portfolio selection strategy.